The Relationship Between Project Based Learning and Communication Skills of Nursing Students - Fairus Sintawati; Ratih Ayu Wulandari (Jurnal Pendidikan dan Sastra Inggris, 2026)
This research aims to determine the relationship between Project Based Learning (PBL) and the communication skills of nursing students. Communication skills are important competencies that nursing students must possess in order to interact effectively with patients, lecturers, and healthcare teams. Therefore, appropriate learning methods are needed to improve students’ communication abilities in the learning process. This study used a quantitative correlational research design. The subjects of this research were nursing students who participated in learning activities using the Project Based Learning method. The data were collected through questionnaires and observation sheets related to students’ communication skills during classroom activities and project presentations. The results of the study showed that there is a positive relationship between Project Based Learning and students’ communication skills. Students who actively participated in project-based activities demonstrated better communication abilities, such as expressing ideas, cooperating in groups, presenting information, and responding to discussions confidently. In addition, Project Based Learning encouraged students to become more active, collaborative, and communicative during the learning process. Therefore, it can be concluded that Project Based Learning has a significant relationship with the communication skills of nursing students. This learning method can be used as an effective strategy to improve students’ communication competence in nursing education.